„Lubiły szczególniej muzykę, która część ich wychowania stanowiła”. Domowa edukacja muzyczna polskich szlachcianek epoki oświecenia - Janicka, Jowita (Studia Edukacyjne, 2021)
The education and upbringing of youth was one of the main issues considered by the aristocracy of Polish-Lithuanian Commonwealth in the age of the Enlightenment. A significant part of this current was music education (learning to play the instruments, singing and dancing) acknowledged as compulsory for women with reading, writing, learning foreign languages and history altogether. Every well-educated woman aristocrat could elegantly play the instrument and sing. They were gaining that knowledge primarily at home from foreign and domestic teachers. Despite the popularity of such education and constant presence of music during many noble balls, ceremonies and social arrangements, it was unfavorable in the eyes of current educational theoreticians and according to them useless. Yet memoirs offer multiple examples of delight about female musical abilities. Furthermore, music as a fundamental part of education was mentioned by women themselves; the shortcomings were punished. It seems that despite educationalists’ complaints music education of women helped them entertain noble guests with their musical talents. Woman with such skills, seeking good and affluent husbands, could successfully conquer male hearts.